THE IMPLEMENTATION OF BUS RAPID TRANSIT (BRT) IN MAKASSAR BASED ON ECONOMIC PERSPECTIVE - Karina Mayasari (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2019)
Transport availability and efficiency affects globally and nationally economic development patterns and can be a boost or a barrier to economic growth within individual nations. Urban transportation has an important role in economic growth because transportation has a characteristic as a derived demand in economy. This research’s aim tofind out the relation between the public transportation to the economy and to find out the reason why the public transportation is needed in a city in Makassar City case. From a theoretical perspective, the possible things that happened in Makassar is there is changes in economic growth cause changes in transport activity, meaning that growth in the demand for travel depends on economic growth. The development of the city has not been integrated with the development of social service and economic services in the area multifunctional and does not follow transit-oriented development, so the volume of movement of the population is very high towards to downtown service centers, whereas housing development should be brought closer to the service centers with mixed function and bus stop for transportation mode transfer. So basically, public transport is a must in Makassar due to its benefits to the economic in Makassar.